Stability Analysis of Cohen–Grossberg Type BAM Neural Network with Piecewise Constant Argument - Wenqing Zheng; Tao Xie; Wenxiang Fang (Discrete Dynamics in Nature and Society)
This paper introduces the stability problems of Cohen–Grossberg type BAM neural network (BAMCGNN) with piecewise constant argument (PCA). By employing the homeomorphism theory, sufficient conditions for the existence and uniqueness of the equilibrium point are obtained; using inequality technique and Lyapunov method, sufficient stability criteria for BAMCGNN with PCA are presented. Finally, a numerical case shows the significance of the results of this paper.